What constitutes victims of toxicity - identifying drivers of toxic victimhood in multiplayer online battle arena games - Kordyaka, Bastian; Laato, Samuli; Weber, Sebastian; Niehaves, Bjoern (Frontiers in Psychology, 2023)
Introduction Toxic behavior (i.e., toxicity) is a pervasive problem in online gaming communities such as League of Legends. This issue arises from factors such as frustrating and stressful in-game experiences and online disinhibition. Prior research on addressing toxicity has focused primarily on the perpetrators and how to mitigate their negative behavior and the consequences. The aim of this study was to approach toxicity from the perspective of the victims instead, and consequently, to investigate the factors that contribute to the experience of victimhood in multiplayer online battle arena games. Methods A global sample of League of Legends and Defense of the Ancients 2 players (n=313) was collected to test hypotheses based on three theoretical approaches drawn from previous work, namely, the online disinhibition effect, social cognitive theory and theory of planned behavior. Participants were asked to complete a survey that included variables related to the three theoretical approaches. Results The results of the study indicated that self-efficacy, and benign and toxic disinhibition, were the most relevant antecedents for the experience of being a victim of toxicity. Accordingly, the findings thus suggest that players with low self-efficacy and high online disinhibition may be more likely to experience victimhood in multiplayer online battle arena games. In general, insights based on our study demonstrate that individual characteristics partially explain why some players are more susceptible to toxic behavior than others. Discussion The study’s results have practical implications for game developers and policymakers, particularly in the areas of community management and player education. For example, game developers may consider incorporating self-efficacy training and disinhibition reduction programs into their games. Overall, this study contributes to the growing body of literature on toxicity in online gaming communities and invites further research into toxicity from the perspective of the victims.